Four decades of declining federal leadership in the federal-state unemployment insurance program - Stephen A. Wandner (W.E. Upjohn Institute for Employment Research, 2019)
The unemployment insurance (UI) program was established in 1935. Unlike other social insurance programs created by the Social Security Act, it was established as a federal-state program. The federal government initially acted as a strong partner working with state agencies that operate the UI program. Over the past four decades, however, the federal role in the UI program has declined because of reductions in federal resources dedicated to the program and weakening policy leadership and programmatic support. As a result, states operate increasingly divergent UI programs, with many programs providing limited access to the program for experienced unemployed workers who are unemployed through no fault of their own. This paper analyzes the declining role of federal leadership and concludes that it has not been an effective force in maintaining and enhancing a program that should be doing more to ameliorate the effects of economy-wide unemployment and helping individual UI recipients to return to work. If the UI system is going to be effective in the future, especially in future recessions, major strengthening of the UI program is necessary.
Keywords: J65; J68; H7; 330; unemployment insurance; public policy; intergovernmental relations